Front Anti Komunis dan Front Pembela Islam: Studi Komparatif dalam Perspektif Sejarah - Adam, Yusril Fahmi; Badrun, Badrun (Fakultas Adab dan Humaniora UIN Raden Fatah, 2023)
This article aims to compare the Anti-Communist Front (FAK) and the Islamic Defenders Front (FPI) in a historical perspective. This research uses a historical method through four stages, namely collecting data or sources (heuristics), source criticism, interpretation, and historiography. In its analysis, this research uses a socio-political approach, so that this research is not only narrative-descriptive, but more analytical-descriptive. The results of this research show that FAK and FPI are two movements that use Islamic ideology as the basic guideline for their movement. FAK and FPI used Islamic ideology as the basis for their struggle due to the influence of Isa Anshary and Rizieq Shihab who belonged to Islamic fundamentalism and made da'wah the key to the start of their movement. Furthermore, FAK and FPI also aim to provide resistance to the PKI and the ideology of communism, and thoughts of liberalism, secularism, and actions that are far from Islamic religious judgments. The conclusion in the article is that the implementation of the FAK and FPI movements can influence socio-political aspects in Indonesia due to the stimulus of Islamic preaching that has been instilled in all FAK and FPI cadres.